Pelatihan Penyusunan Perangkat Pembelajaran Inovatif bagi Guru - Ali Imran; Wahyu Hananingsih (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This community service activity aims to improve the capacity of high school teachers in developing innovative learning tools based on the Independent Curriculum. The training took the form of a one-day intensive workshop at Raudlatul Jannah An Nur Darek Islamic High School in Central Lombok, and was attended by 15 teachers from various subject groups. The training materials covered the concept of innovative teaching tools, 21st-century learning models (such as Project-Based Learning and Problem-Based Learning), and practical lessons and digital teaching media development using Canva and Wordwall. Formative evaluation was conducted through participant observation and the quality of the products produced by participants. Results showed a significant increase in teacher understanding and skills, with all participants able to develop lesson plans that included achievement-based learning objectives, active learning, and HOTS-based assessments. Furthermore, the training fostered positive attitudes toward the use of technology in learning and the importance of contextual instructional design. This training demonstrated that a practical and participatory approach can effectively improve teacher competency in a short time. This training model is worthy of replication as a continuous professional development effort for teachers in various regions.